Polyarylene sulfide film

JP2026167496APending Publication Date: 2026-10-14TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2026034012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-04
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明により、高温環境下での耐電圧特性に優れ、誘電体として用いることでフィルムコンデンサの長期安定性向上させることができる、ポリアリーレンスルフィドフィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167496000001
    Figure 2026167496000001
  • Figure 2026167496000002
    Figure 2026167496000002
  • Figure 2026167496000003
    Figure 2026167496000003
Patent Text Reader

Abstract

The present invention aims to solve the above problems and provide a polyarylene sulfide film that has excellent voltage resistance characteristics in high-temperature environments and can be used as a dielectric to miniaturize film capacitors. [Solution] When the Raman orientation parameter in the longitudinal direction is Rd1 and the Raman orientation parameter in the width direction is Rd2, (Rd1 + Rd2) / 2 is between 8.3 and 15.0. The thermal shrinkage rate in the longitudinal direction after heating at 170°C for 30 minutes is between -5.0% and 5.0%. Polyarylene sulfide film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a polyarylene sulfide film. [Background technology]

[0002] Polyphenylene sulfide film, one type of polyarylene sulfide film, is disclosed in Patent Document 1, etc. (Hereafter, polyphenylene sulfide may be referred to as PPS). Furthermore, Patent Document 2, etc., proposes that by using PPS film as the dielectric of a film capacitor, it is possible to provide a film capacitor with excellent heat resistance, frequency characteristics, temperature characteristics, etc.

[0003] However, the film capacitors described above have a drawback: their manufacturing process, specifically winding, cutting, and molding, has a narrow range of manufacturing conditions, and insufficient control of these conditions can lead to variations in the physical properties within the film surface, resulting in an increase in defective products due to low-voltage breakdown. Furthermore, these film capacitors often short-circuit without self-healing when low-voltage breakdown occurs, and also have other drawbacks such as increased defect rates and reduced reliability during use.

[0004] To overcome these drawbacks, there have been proposals to improve the properties of PPS films using polymer blends or alloys (Patent Documents 3-5). For example, Patent Document 3 proposes a method to improve the tear resistance of a PPS film by blending PPS with polyetherimide and controlling the dispersion diameter of the polyetherimide to be 30 μm or less, while Patent Documents 4 and 5 propose a method to improve the dielectric strength of a film by compatibilizing polyetherimide with PPS and forming a film. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 54-142275 [Patent Document 2] Japanese Patent Application Publication No. 57-187327 [Patent Document 3] Japanese Patent Publication No. 158312 / 1983 [Patent Document 4] Japanese Patent Publication No. 2001-261959 [Patent Document 5] Japanese Patent Publication No. 2008-280508 [Overview of the project] [Problems that the invention aims to solve]

[0006] However, the method described in Patent Document 3 only improves the tear resistance of the resulting PPS film, and does not consider improving its electrical properties or the characteristics of film capacitors when used as a dielectric. Furthermore, the methods described in Patent Documents 4 and 5 have difficulty achieving voltage resistance at high temperatures suitable for automotive applications and other uses where reliability is required, due to issues such as the generation of foreign matter as a side reaction by the compatibilizer promotes crosslinking of the resin, and the bleeding out of side reaction components over time.

[0007] The present invention aims to solve the above problems and provide a polyarylene sulfide film that has excellent voltage resistance characteristics in high-temperature environments and can be used as a dielectric to miniaturize film capacitors. [Means for solving the problem]

[0008] The polyarylene sulfide film of the present invention has the following configuration to solve the above problems. Specifically, the polyarylene sulfide film of the present invention is a polyarylene sulfide film in which, when the Raman orientation parameter in the longitudinal direction is Rd1 and the Raman orientation parameter in the width direction is Rd2, (Rd1 + Rd2) / 2 is 8.3 or more and 15.0 or less, and the thermal shrinkage rate in the longitudinal direction after heating at 170°C for 30 minutes is 5.0% or less and 5.0% or more.

[0009] Furthermore, the polyarylene sulfide film of the present invention can be in the following forms, and can be used to obtain metal laminates, film capacitors, power control units, electric vehicles, and electric aircraft. (1) A polyarylene sulfide film in which, when the longitudinal Raman orientation parameter is Rd1 and the widthwise Raman orientation parameter is Rd2, (Rd1 + Rd2) / 2 is between 8.3 and 15.0, and the longitudinal thermal shrinkage rate after heating at 170°C for 30 minutes is between -5.0% and 5.0%. (2) The polyarylene sulfide film described in (1), which contains a resin with a glass transition temperature of 170°C or higher and 300°C or lower. (3) The polyarylene sulfide film according to (1) or (2), wherein the Sv of at least one surface is 0.00010 μm or more and 1.0 μm or less. (4) A polyarylene sulfide film according to any one of (1) to (3), wherein, in the molecular weight distribution measured by GPC, the dw / dlogM value of the polyarylene sulfide component with logM=5 is 0.70 or more and 10 or less. (5) A polyarylene sulfide film according to any one of (1) to (4), comprising a polyethersulfone. (6) A polyarylene sulfide film according to any one of (1) to (5), wherein the silicon atom content is 0 ppm or more and 3500 ppm or less when the total mass of the film is 100% by mass. (7) A polyarylene sulfide film according to any one of (1) to (6), wherein at least one of the outermost layers has a resin layer A in which polyarylene sulfide is not the main component. (8) The polyarylene sulfide film according to (7), wherein the resin layer A comprises at least one compound selected from the group consisting of urethane acrylate polymer, acrylate polymer, urethane methacrylate polymer, methacrylate polymer, aliphatic polyether, aliphatic polyester, aliphatic polyamide, polyurethane, and polyurea. (9) A metal laminate having a metal layer on at least one surface of a polyarylene sulfide film as described in any of (1) to (8). (10) A film capacitor made using the metal laminate described in (9). (11) A power control unit having the film capacitor described in (10). (12) An electric vehicle having the power control unit described in (11). (13) An electric aircraft having the power control unit described in (11). [Effects of the Invention]

[0010] The present invention provides a polyarylene sulfide film that exhibits excellent voltage resistance characteristics in high-temperature environments and can improve the long-term stability of film capacitors when used as a dielectric. [Modes for carrying out the invention]

[0011] The polyarylene sulfide film of the present invention will now be described. The polyarylene sulfide film of the present invention is a polyarylene sulfide film in which, when the Raman orientation parameter in the longitudinal direction is Rd1 and the Raman orientation parameter in the width direction is Rd2, (Rd1 + Rd2) / 2 is 8.3 or more and 15.0 or less, and the thermal shrinkage rate in the longitudinal direction after heating at 170°C for 30 minutes is -5.0% or more and 5.0% or less.

[0012] In the present invention, a polyarylene sulfide film refers to a film made by melt-molding a resin composition mainly composed of a polyarylene sulfide (hereinafter sometimes referred to as PAS) resin into a sheet. The PAS film may be stretched, and preferably biaxially stretched.

[0013] In the present invention, that a PAS-based resin is the main constituent component (main component) means that the PAS-based resin is contained in an amount of more than 50 mass% and 100 mass% or less, preferably 60 mass% or more and 100 mass% or less, more preferably 70 mass% or more and 100 mass% or less. If the content of the PAS-based resin is 50 mass% or less, the heat resistance, dimensional stability, and mechanical properties, which are characteristics of the film, may be impaired. Hereinafter, the main component can be interpreted in the same manner.

[0014] In the present invention, the PAS-based resin is a homopolymer or copolymer containing more than 50 mol% and 100 mol% or less of the repeating unit "-(Ar-S)-", based on 100 mol% of all structural units constituting the resin. Here, Ar means an arylene group, and examples of Ar include groups represented by the following formula (A) to formula (K). In addition, hereinafter, the structural unit contained in the largest amount among all the structural units may be referred to as the main structural unit.

[0015]

Chemical Formula

[0016] (Wherein R1 and R2 are substituents selected from hydrogen, an alkyl group, an alkoxy group, and a halogen group, and R1 and R2 may be the same or different.) As the structural unit of the PAS-based resin, the p-arylene sulfide unit represented by the above formula (A) is preferable, and typical examples thereof include polyphenylene sulfide, polysulfone, polyether sulfone, polyphenylene sulfide sulfone, polyphenylene sulfide ketone and the like. As a particularly preferable p-arylene sulfide unit, a p-phenylene sulfide unit is exemplified from the viewpoints of the physical properties and economic efficiency of the obtained polyarylene sulfide film.

[0017] The PAS resin used in the PAS film of the present invention preferably contains p-phenylene sulfide units represented by the following structural formula, with a concentration of more than 50 mol% and up to 100 mol%, more preferably between 80 mol% and 99.9 mol% of the total constituent units. In other words, the PAS film of the present invention preferably contains polyphenylene sulfide, with a concentration of more than 50% and up to 100% by mass, when the total mass of the components constituting the PAS film is taken as 100% by mass. By adopting this configuration, the PAS film of the present invention can be made to obtain a polyarylene sulfide film with excellent heat resistance and voltage resistance characteristics.

[0018] [ka]

[0019] Furthermore, the PAS resin may contain copolymerized constituent units represented by the following chemical formula in an amount of 0.01 mol% to 20 mol% of the total constituent units. The form of the copolymer is not particularly limited, but from the viewpoint of compatibility, a random copolymer is preferred.

[0020] The following are examples of preferred copolymer units, with the m-phenylene sulfide unit being particularly preferred.

[0021] [ka]

[0022] [ka]

[0023] [ka]

[0024] (Here, X represents alkylene, CO, and SO2 units.)

[0025] [ka]

[0026] [ka]

[0027] (Here, R represents an alkyl, nitro, phenylene, or alkoxy group.) Furthermore, the PAS resin constituting the PAS film of the present invention may contain various additives such as antioxidants, heat stabilizers, antistatic agents, and antiblocking agents, to the extent that they do not impair the effects of the present invention.

[0028] The PAS film of the present invention may contain inert particles or other thermoplastic resins (X) from the viewpoint of improving processability. From the viewpoint of film-forming properties, the content of inert particles or other thermoplastic resins is preferably 1% by mass or less when the total mass of the PAS film is 100% by mass, and from the viewpoint of improving processability, it is preferably 0.01% by mass or more.

[0029] Examples of inert particles suitable for application to the PAS film of the present invention include inorganic particles such as silica, alumina, calcium carbonate, barium carbonate, barium titanate, barium sulfate, calcium silicate, magnesium oxide, titanium oxide, and zinc oxide. Among these, calcium carbonate is preferred from the viewpoint of manufacturing cost. These components may be used individually or in combination of multiple types.

[0030] The PAS film of the present invention may have a laminated structure having two or more layers in which PAS resin is the main component, from the viewpoint of adjusting stretchability and processability. Furthermore, examples of laminated structures include a 3-layer structure of A / B / C, a 3-layer structure of A / B / A, and a 2-layer structure of A / B, where layers containing different components are made up of layers A, B, C, etc.

[0031] From the viewpoint of improving the voltage resistance, it is important that the PAS film of the present invention has a ratio of (Rd1 + Rd2) / 2 of 8.3 to 15.0, where Rd1 is the Raman orientation parameter in the longitudinal direction and Rd2 is the Raman orientation parameter in the width direction.

[0032] From the above viewpoint, (Rd1+Rd2) / 2 is preferably 8.6 or higher, more preferably 9.0 or higher. Increasing (Rd1+Rd2) / 2 can increase the withstand voltage when used as a film capacitor. From the above viewpoint, the higher (Rd1+Rd2) is better, but from the viewpoint of feasibility, the upper limit is 15.0.

[0033] There are no particular limitations on how to increase (Rd1+Rd2) / 2, but effective methods include incorporating a resin with a glass transition temperature of 170°C or higher, using a PAS raw material in which the dw / dlogM value of the polyarylene sulfide logM=5 component in the molecular weight distribution measured by GPC is 0.70 or higher, and performing stretching at a suitable stretching ratio described later. In particular, (Rd1+Rd2) / 2 can be effectively increased by incorporating a resin with a glass transition temperature of 170°C or higher, increasing the stretching ratio in the longitudinal direction, and using a PAS raw material in which the dw / dlogM value of the polyarylene sulfide logM=5 component in the molecular weight distribution measured by GPC is 0.70 or higher. Rd1 and Rd2 can be measured by Raman spectroscopy, and details of the measurement method will be described later.

[0034] From the viewpoint of dimensional stability when used as a dielectric in a film capacitor, it is important that the PAS film of the present invention has a longitudinal thermal shrinkage rate of -5.0% or more and 5.0% or less after heating at 170°C for 30 minutes. From the above viewpoint, the longitudinal thermal shrinkage rate after heating at 170°C for 30 minutes is preferably 4.0% or less, and more preferably 3.5% or less. On the other hand, from the same viewpoint, the lower limit of the longitudinal thermal shrinkage rate after heating at 170°C for 30 minutes is preferably -3.0%, and more preferably -1.0%. By setting the longitudinal thermal shrinkage rate after heating at 170°C for 30 minutes within the above range, the dimensional stability of the PAS film of the present invention when used as a capacitor can be improved.

[0035] Methods for achieving a longitudinal heat shrinkage rate of -5.0% to 5.0% after heating at 170°C for 30 minutes include, for example, providing a relaxation step after longitudinal stretching, controlling the temperature of the relaxation step after longitudinal stretching within a suitable range, or performing longitudinal stretching at a suitable magnification range described later. Details of the method for measuring the heat shrinkage rate will be described later.

[0036] In the PAS film of the present invention, "longitudinal direction" refers to the direction corresponding to the flow direction in the film manufacturing process (hereinafter sometimes referred to as "MD"), and if the film sample is in the shape of a reel, roll, winding body, film capacitor, etc., this corresponds to the film winding direction. Furthermore, "width direction" refers to the direction perpendicular to the longitudinal direction within the film surface (hereinafter sometimes referred to as "TD"). On the other hand, in the case of a film where it is unclear from the appearance of the film which direction is the longitudinal direction, lines are drawn at 15° intervals based on an arbitrary straight line on the film plane, slit-shaped film pieces parallel to each line are sampled, and the breaking strength is determined using a tensile tester. The direction that gives the maximum breaking strength is considered to be the width direction of the film, and the direction perpendicular to the width direction is considered to be the longitudinal direction. The breaking strength can be measured by the following procedure.

[0037] First, a rectangular piece of PAS film (width (short side) 10 mm × length (long side) 150 mm), cut with the length direction as the longer side, is used as the measurement sample. Next, the sample is set in a tensile testing machine (for example, Orientec's "Tensilon" (registered trademark) UCT-100 can be used) with an initial chuck distance of 20 mm, and a tensile test of the film is performed in a room at 23°C at a tensile speed of 300 mm / min. At this time, the position of the sample in the longitudinal direction is adjusted so that the center of the sample is near the middle of the chucks. The load applied to the film at the time of sample fracture is read, and the value obtained by dividing it by the cross-sectional area of ​​the sample before the test (film thickness × width (10 mm)) is calculated as the breaking strength (unit: MPa).

[0038] The PAS film of the present invention preferably contains a resin with a glass transition temperature of 170°C to 300°C (hereinafter, this resin is referred to as thermoplastic resin (X)). By including a thermoplastic resin (X) whose glass transition temperature falls within a suitable range, the (Rd1+Rd2) / 2 ratio can be increased, thereby increasing the dielectric strength when used as a film capacitor. From the viewpoint of improving stability during film formation, the glass transition temperature of the thermoplastic resin (X) is more preferably 250°C or lower. On the other hand, from the viewpoint of improving dimensional stability when used at 150°C, the glass transition temperature of the thermoplastic resin (X) is more preferably 200°C or higher.

[0039] From the viewpoint of increasing the dielectric strength when used as a film capacitor, the content of thermoplastic resin (X) is preferably 0.010% by mass or more, more preferably 0.50% by mass or more, and even more preferably 1.5% by mass or more, when the total mass of the PAS film is considered as 100% by mass. On the other hand, from the viewpoint of improving film-forming properties, it is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 15% by mass or less.

[0040] In the PAS film of the present invention, suitable thermoplastic resins (X) include, for example, polyarylate, polyphenylene ether, polyetherimide, polysulfone, polyphenylsulfone, and polyethersulfone. However, from the viewpoint of affinity with the PAS resin, polysulfone, polyphenylsulfone, and polyethersulfone are preferred. These components may be used individually, in combination of multiple types, or in combination with the aforementioned inert particles.

[0041] In the PAS film of the present invention, it is preferable that the Sv of at least one surface is 0.00010 μm or more and 1.0 μm or less. In the present invention, Sv refers to the maximum valley depth measured by the method described later. By making the surface Sv 1.0 μm or less, the number of insulation defects can be reduced, improving the lifespan and reliability when used as a film capacitor. From the above viewpoint, the lower the Sv, the better, but from the viewpoint of feasibility, it is preferable that it be 0.00010 μm or more.

[0042] Furthermore, as a method for keeping Sv within the aforementioned preferred range while ensuring processability, it is preferable to incorporate a resin (thermoplastic resin (X)) with a glass transition temperature of 170°C or higher into the PAS film of the present invention and reduce the content of inorganic particles with a diameter of 1.0 μm or more.

[0043] In the PAS film of the present invention, it is preferable that the dw / dlogM value of the polyarylene sulfide component with logM=5 in the molecular weight distribution measured by GPC is 0.70 or more and 10 or less. A high dw / dlogM value means that the PAS film is composed of more uniform high molecular weight components, and this configuration makes it easier to produce a PAS film with fewer insulation defects. Furthermore, having the dw / dlogM value within the above range can increase (Rd1+Rd2) / 2, thereby increasing the dielectric strength of the PAS film. From the above viewpoint, it is more preferable that the dw / dlogM value be 0.73 or more. On the other hand, from the viewpoint of film-forming properties, it is more preferable that the dw / dlogM value be 5.0 or less, and even more preferable that be 1.0 or less.

[0044] To ensure that the dw / dlogM of the logM=5 component of PAS in PAS film is between 0.70 and 10, it is effective to use PAS where the dw / dlogM of the logM=5 component falls within the above range, or to increase the proportion of such PAS.

[0045] The PAS film of the present invention preferably has a silicon atom content of 0 ppm or more and 3500 ppm or less when the total mass of the film is 100% by mass. Since substances containing silicon atoms are the starting point for dielectric breakdown of the PAS film, insulating defects can be reduced by setting the silicon atom content within the above preferred range. From the above viewpoint, the silicon atom content is more preferably 2500 ppm or less, even more preferably 1500 ppm or less, and particularly preferably 300 ppm or less. From the above viewpoint, the lower the silicon atom content, the better, and the theoretical upper and lower limits are 0 ppm.

[0046] The PAS film of the present invention preferably has a resin layer A in at least one outermost layer in which polyarylene sulfide is not the main component. That is, it is preferable to have a resin layer A in which the polyarylene sulfine content is less than 50% by mass when the total mass of the layer is taken as 100% by mass. Furthermore, it is preferable that the resin layer A contains at least one compound selected from the group consisting of urethane acrylate polymer, acrylate polymer, urethane methacrylate polymer, methacrylate polymer, aliphatic polyether, aliphatic polyester, aliphatic polyamide, polyurethane, and polyurea.

[0047] Because these compounds are softer than PAS, by providing resin layer A, when a metal laminate, which consists of a PAS film with a metal layer, is wound into a film capacitor shape and subjected to prolonged heat treatment, winding misalignment and deformation can be suppressed, thereby improving the reliability of the resulting film capacitor.

[0048] From the above viewpoint, it is more preferable that the resin layer A contains at least one resin from the group consisting of urethane acrylate polymer, urethane methacrylate polymer, polyurethane, and polyurea, and even more preferable from the viewpoint of increasing moisture and heat resistance, it contains at least one resin from the group consisting of urethane acrylate polymer and urethane methacrylate polymer. Urethane acrylate polymer refers to a compound obtained by polymerizing acrylate containing urethane bonds. Acrylate polymer refers to a compound obtained by polymerizing acrylate other than urethane acrylate polymer. Aliphatic polyether, aliphatic polyester, and aliphatic polyamide refer to resins having a structure in which aliphatic hydrocarbon groups are linked by ether bonds, ester bonds, and amide bonds, respectively. Note that two or more resins from the above resin group may be selected and mixed, or at least one compound containing two or more constituent units of the above resin group may be included.

[0049] From the viewpoint of reducing the size when used as a film capacitor and improving processability, the thickness of the PAS film of the present invention is preferably more than 0.5 μm and 10.0 μm or less. From the same viewpoint, the thickness of the PAS film of the present invention is more preferably more than 2.0 μm. On the other hand, the thickness of the PAS film of the present invention is more preferably 6.0 μm or less.

[0050] In the PAS film of the present invention, the thickness of the resin layer B is preferably 0.5 μm or more and less than 10.0 μm, from the viewpoint of reducing the size when used as a film capacitor and ensuring processability. From the same viewpoint, the thickness of the B layer is more preferably 2.0 μm or more. On the other hand, the thickness of the B layer is more preferably less than 6.0 μm.

[0051] In the PAS film of the present invention, the thickness of resin layer A is preferably smaller than the thickness of resin layer B, more preferably 20% or less of the thickness of resin layer B, and even more preferably 5% or less, from the viewpoint of improving performance when used as a film capacitor. On the other hand, from the viewpoint of uniformly forming resin layer B, the thickness of resin layer B is preferably 50 nm or more.

[0052] Next, the method for producing the PAS film of the present invention will be explained using polyphenylene sulfide resin (hereinafter sometimes abbreviated as PPS resin) as the PAS-based resin, with a two-layer structure consisting of resin layer A and a layer mainly composed of PAS (hereinafter referred to as resin layer B) as an example. However, the PAS film of the present invention may have a structure that does not include resin layer A, or a structure of two or more layers having other layers.

[0053] First, sodium sulfide and p-dichlorobenzene are combined and reacted under high temperature and pressure in an amide-based polar solvent such as N-methyl-2-pyrrolidone (NMP). Copolymer components such as m-dichlorobenzene and trihalobenzene can be added as needed. Caustic potash or alkali metal carboxylic acid salts are added as polymerization modifiers and the polymerization reaction is carried out at 240-290°C. After polymerization, the polymer is cooled, filtered as an aqueous slurry, and a wet granular polymer is obtained. This granular polymer is washed by adding an amide-based polar solvent and stirring at a temperature of 30-100°C, washed several times with deionized water at 30-80°C, washed several times with an aqueous solution of a metal salt such as calcium acetate, and then dried to obtain PPS powder.

[0054] Next, the PPS film that will become resin layer B is manufactured by the following method. First, PPS chips that have been dried under reduced pressure at 170°C for 3 hours as needed are mixed with a masterbatch containing the above-mentioned inert particles, etc., in a predetermined ratio and supplied to a full-flight single-screw extruder set to a molten section of 320-360°C. After passing through a filter, it is extruded in a sheet form from a T-die type die. This molten sheet is rapidly cooled and solidified by adhering it to a cooling drum with a surface temperature of 20-60°C while applying an electrostatic charge, thereby obtaining an unoriented, unstretched film.

[0055] Next, the unstretched film obtained above is biaxially stretched using a sequential biaxial stretcher or a simultaneous biaxial stretcher at a temperature of 80°C to 150°C, and then subjected to a one-stage or multi-stage heat treatment at a temperature of 220 to 290°C to obtain a biaxially oriented film containing crystalline component B. As for the stretching method, sequential biaxial stretching (a stretching method that combines stretching in one direction at a time, such as stretching in the longitudinal direction followed by stretching in the width direction), simultaneous biaxial stretching (a method that stretches in the longitudinal and width directions simultaneously), or a method that combines these can be used. Here, sequential biaxial stretching, in which stretching is performed first in the longitudinal direction and then in the width direction, is given as an example.

[0056] The unstretched film is heated with a group of heating rolls and stretched in the longitudinal direction (MD direction) at a predetermined magnification in one or more stages (MD stretching). The stretching magnification in the longitudinal direction is preferably 2.3 times or more, more preferably 2.9 times or more, and particularly preferably 3.4 times or more, from the viewpoint of increasing (Rd1 + Rd2) / 2, while from the viewpoint of controlling the thermal shrinkage rate in the longitudinal direction, it is preferably 5.0 times or less, more preferably 4.5 times or less, particularly preferably 3.9 times or less, and particularly preferably 3.7 times or less. The stretching temperature is preferably in the range of 80°C to 150°C. After that, it is cooled with a group of cooling rolls at 20 to 50°C. In the case of multi-stage stretching, the stretching magnification referred to here is the stretching magnification after all stretching is completed.

[0057] Furthermore, from the viewpoint of keeping the thermal shrinkage rate in the longitudinal direction within the aforementioned preferred range, it is preferable to perform a relaxation treatment in the longitudinal direction after longitudinal stretching at a temperature of -20°C to +15°C, preferably -4°C to +10°C or lower. The relaxation treatment is preferably performed by controlling the peripheral speed of the roll to shrink the material by 1.0% to 25% in the longitudinal direction, preferably 1.0% to 4.0% in the longitudinal direction.

[0058] A common method for stretching in the width direction (TD direction) following MD stretching is, for example, the use of a tenter. Stretching in the width direction (TD stretching) is performed by gripping both ends of the uniaxially oriented film in the width direction with multiple clips, guiding it to a tenter, and widening the distance between opposing clips. The stretching temperature is preferably in the range of 80°C to 150°C, and more preferably in the range of 90°C to 130°C. The stretching ratio in the width direction is preferably 2.0 times or more, and more preferably 3.0 times or more, from the viewpoint of the film's flatness. On the other hand, it is preferably 5.0 times or less, even more preferably 4.5 times or less, and particularly preferably 3.7 times or less.

[0059] Next, the stretched film is subjected to a heat-setting process under tension. A single or multi-stage heat treatment is performed at a temperature in the range of 185 to 280°C to obtain a biaxially oriented film containing crystalline component B. Then, the film is cooled to room temperature, and if necessary, relaxed in the longitudinal and widthwise directions, and wound up to obtain a biaxially oriented PAS film.

[0060] Methods for forming resin layer A on one of the outermost layers of the biaxially oriented PPS film, with resin layer B being the resin layer, include coating the resin layer B with a solution or liquid raw material using a coater and then drying it, or vacuum depositing the resin layer A raw material onto resin layer B. When forming resin layer A by coating one side of resin layer B with the raw material, the coated surface of the PPS film that will become resin layer B may be subjected to a surface treatment such as corona discharge treatment beforehand. Performing a surface treatment such as corona discharge treatment improves the wettability of the coating composition for forming resin layer A onto the coated surface. As a result, the repulsion of the coating composition is suppressed, and it becomes easier to achieve a uniform coating thickness.

[0061] The method for forming resin layer A is not particularly limited, but as an example, a method for forming resin layer A using a bar coater is described. First, a coating solution is prepared by mixing 100 parts by mass of acrylate, 0.1 to 5 parts by mass of α-hydroxyalkylphenone, which is a photopolymerization initiator, and 800 to 1000 parts by mass of 2-butanone. The coating solution, prepared so that the cured coating thickness is 40 nm to 500 nm, is applied to the corona discharge treated surface of the PPS film that will become resin layer B using a bar coater. This is then introduced into a drying oven at 80°C to 100°C and dried for 30 seconds to 2 minutes. Subsequently, it is introduced into a UV irradiation device at an illuminance of 40 mW / cm². 2 ~70mW / cm 2 , irradiation amount 0.05J / cm 2 ~0.3J / cm 2 By curing the coating under conditions of an oxygen concentration of 80 ppm to 300 ppm, resin layer A can be formed.

[0062] The metal laminate of the present invention will now be described. From the viewpoint of integration, the metal laminate of the present invention has a metal layer on at least one surface of the PAS film of the present invention. Furthermore, for the purpose of enhancing self-healing properties, if the PAS film has a resin layer A, it is more preferable to have a metal laminate having a metal layer on the resin layer A.

[0063] The thickness of the metal layer is preferably in the range of 1 nm to 100 nm, more preferably 5 nm to 80 nm, and even more preferably 10 nm to 50 nm. The surface resistivity of the metal layer is preferably in the range of 0.1 Ω / sq to 10 Ω / sq, more preferably 2.0 Ω / sq to 8.0 Ω / sq, and even more preferably 3.0 Ω / sq to 6.0 Ω / sq. This is because a surface resistivity of 0.1 Ω / sq or higher improves self-healing properties. Conversely, keeping the surface resistivity of the metal layer below 10 Ω / sq reduces the deterioration of the dielectric loss tangent. The surface resistivity of the metal layer can be adjusted by adjusting the thickness of the metal layer.

[0064] The PAS film of the present invention exhibits excellent voltage resistance characteristics in high-temperature environments. Therefore, taking advantage of these characteristics, it can be suitably used as a film for film capacitors, and further suitable for use as an electrical insulating material for motors and transformers, circuit board material, lithium-ion battery material, fuel cell material, diaphragm, and the like. In particular, its high voltage resistance allows for miniaturization of products, and its excellent long-term stability enhances product reliability, making it suitable for use in inverters for mobility devices such as electric vehicles and electric aircraft, as well as film capacitors for generators.

[0065] The PAS film of the present invention is preferably used as a dielectric in film capacitors, but is not limited to the type of film capacitor. Specifically, in terms of electrode configuration, it may be either a foil-wound capacitor or a metal-deposited film capacitor, and is also preferably used in oil-immersion type capacitors impregnated with insulating oil or dry-type capacitors that do not use insulating oil at all. Furthermore, in terms of shape, it may be either a wound type or a laminated type. Among these, due to the characteristics of the PAS film of the present invention, it is preferable to use it as a metal-deposited film capacitor including a metal laminate. As a method for forming the metal layer, for example, vacuum deposition, sputtering, ion plating, plating, etc., can be used. Among these methods, vacuum deposition is preferred because it is superior in productivity. When the metal layer is deposited, oil deposition or tape deposition methods can be used. The deposition pattern of the metal layer is not particularly limited, but preferred patterns include, for example, T-margin patterns, honeycomb patterns, mosaic patterns, etc.

[0066] The metal component of the aforementioned metal layer is not particularly limited, but aluminum or an alloy of aluminum and zinc is preferably used. Alternatively, other metal components such as nickel, copper, gold, silver, or chromium can be deposited simultaneously or sequentially with aluminum to form the metal layer. A protective layer, such as oil, can also be provided on the deposited film. When laminating a metal layer onto a film having a resin layer A by vapor deposition, a surface treatment such as corona discharge may be performed on the deposition surface of the film capacitor before vapor deposition. Such surface treatment can improve the adhesion of the deposited metal to the surface.

[0067] Next, the film capacitor of the present invention will be described. The film capacitor of the present invention is made using the metal laminate of the present invention. The film capacitor of the present invention can be used as part of an automotive inverter and / or converter (for example, an inverter for a hybrid electric vehicle, a converter for a hybrid electric vehicle, an inverter for an electric vehicle, a converter for an electric vehicle, etc.).

[0068] The following describes the power control unit, electric vehicle, and electric aircraft of the present invention. The power control unit of the present invention has the film capacitor of the present invention. The power control unit is a system for managing power in electric vehicles, electric aircraft, and the like, which have mechanisms driven by electricity. By equipping the power control unit with the film capacitor of the present invention, it is possible to miniaturize the power control unit itself, improve its heat resistance and efficiency, and as a result, improve fuel efficiency.

[0069] The electric vehicle of the present invention is equipped with the power control unit of the present invention. Here, an electric vehicle refers to an automobile having a mechanism that is driven by electricity, such as an electric vehicle, hybrid vehicle, or fuel cell vehicle. As described above, the power control unit of the present invention can be miniaturized and also has excellent heat resistance and efficiency, so when an electric vehicle is equipped with the power control unit of the present invention, it leads to improved fuel efficiency and other benefits.

[0070] The electric aircraft of the present invention is equipped with the power control unit of the present invention. Here, an electric aircraft refers to an aircraft having an electric drive mechanism, such as a manned electric aircraft or a drone. As described above, the power control unit of the present invention can be miniaturized and also has excellent heat resistance and efficiency, so when an electric aircraft is equipped with the power control unit of the present invention, it leads to improved fuel efficiency and other benefits. [Examples]

[0071] (1) Molecular weight, dw / dlog(M) The molecular weight of the PAS resin was calculated in polystyrene equivalent using gel permeation chromatography (GPC), a type of size exclusion chromatography (SEC). The GPC measurement equipment and conditions are shown below. Device: SSC-7110 manufactured by Senshu Science Co., Ltd. Columns: Showa Denko "Shodex" (registered trademark) UT-G + Shodex UT-806M x 2 Eluent: 1-Chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-temperature bath temperature: 250℃ Pump constant temperature bath temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300μL (concentration: 0.1% by mass) Standard sample: Polystyrene.

[0072] dw / dlog(M) was obtained using the following method. First, the intensity detected by the detector was plotted on a curve (elution curve) with elution time on the x-axis and detection intensity on the y-axis, and a calibration curve of elution time and molecular weight was created using polystyrene as a standard sample. Using this calibration curve, the elution time of the sample was converted to the logarithm of molecular weight (log(M)) on the elution curve, and a molecular weight distribution curve was obtained with elution time on the x-axis and detection intensity on the y-axis. Next, an integral molecular weight distribution curve for log(M) was obtained, where the total area enclosed by the molecular weight distribution curve and the straight line (x-axis) where the intensity is 0 is set to 100%. Then, by differentiating this integral molecular weight distribution curve with respect to log(M), a graph of dw / dlog(M) for log(M) can be obtained (generally called a differential molecular weight distribution curve). The series of operations up to obtaining the differential molecular weight distribution curve was performed using the analysis software built into the GPC measuring instrument. From the obtained differential molecular weight distribution curve, the value of dw / dlog(M) for the component with logM=5 was read. This measurement was repeated three times, and the average of the three values ​​of dw / dlog(M) for the component with logM=5 was recorded as the dw / dlog(M) value for the component with logM=5 in the PAS resin.

[0073] (2) Raman orientation parameter (Rd1 + Rd2) / 2 The film was cut into 5cm x 5cm pieces so that its longitudinal and widthwise sides corresponded to the sides of a square. Using the following apparatus configuration, a Raman spectrum was obtained by irradiating the center of the film with polarized light whose polarization direction was aligned with the longitudinal direction from the surface direction, with an arbitrary surface as the top surface. Next, the wavenumber 1080 cm⁻¹ in the Raman spectrum was obtained. -1The signal strength is read and designated as I1080, wavenumber 750 cm. -1 The signal intensity was read and set to I750. From I1080 and I750, the longitudinal Raman orientation parameter Rd1 was calculated based on the following Raman orientation parameter formula.

[0074] Raman orientation parameter = (I1080 / I750) Next, a Raman spectrum was obtained by irradiating the surface with polarized light whose polarization direction was aligned from the surface direction to the width direction. Similarly, I1080 and I750 were read, and the Raman orientation parameter Rd2 in the width direction was calculated based on the formula for the Raman orientation parameter.

[0075] From the obtained Rd1 and Rd2, (Rd1+Rd2) / 2 was calculated. Furthermore, the same measurement process was repeated four times at four points where the irradiation position was shifted by -2mm, -1mm, +1mm, and +2mm in the width direction from the center of the film. The average of the (Rd1+Rd2) / 2 values ​​obtained from these five measurements was adopted as the (Rd1+Rd2) / 2 value for the film in question. • Equipment: Near-infrared Raman spectrometer (model PDP320, manufactured by PhotonDesign) Conditions: Measurement mode; Micro-Raman Objective lens; 100x magnification Beam diameter: 1 μm Light source: YAG laser / 1064nm Laser power: 1W Diffraction grating; Single 300, 900 gr. / mm Slit: 100 μm Detector; InGaAs.

[0076] (3) Film thickness A point was arbitrarily selected at the center of the film's width, and the thickness was measured at 30 locations at 5 cm intervals along the longitudinal direction from that point, using a contact-type electronic micrometer (K-312A) manufactured by Anritsu Corporation, under conditions of 23°C and 65% RH. The sample average of these 30 thicknesses was defined as the film thickness. The coefficient of variation of the film thickness was calculated according to the following formula. Coefficient of variation of thickness (%) = (Sample standard deviation of film thickness) / (Sample mean of film thickness) × 100 (4) Thickness of resin layer A Using a microtome, ultrathin sections with a width-to-thickness cross-section of 5 mm were prepared, and these sections were coated with platinum to serve as observation samples. Next, the cross-sections were observed using a Hitachi S-4800 field emission differential electron microscope at an acceleration voltage of 1.0 kV, and the thickness of resin layer A was measured from an arbitrary point in the observed image. The observation magnification was 10,000x. Furthermore, the same measurement was performed a total of 20 times, and the average value was taken as the thickness of resin layer A.

[0077] (5) Glass transition temperature of resin The glass transition temperature of the resin was measured in accordance with JIS K7121-1987. Using a differential scanning calorimeter (Seiko Instruments EXSTAR DSC6220), 3 mg of resin was heated from 30°C to 350°C at a rate of 40°C / min in a nitrogen atmosphere, held at 350°C for 5 minutes, and then cooled to 30°C at a rate of 40°C / min. After holding at 20°C for 5 minutes, the resin was reheated from 30°C to 350°C at a rate of 40°C / min. The glass transition temperature was calculated from the DSC curve obtained during the reheating process using the following formula. If multiple endothermic peaks were observed in a single measurement, the peak temperature of the endothermic peak with the highest peak temperature was used as the peak temperature for that measurement. Glass transition temperature = (Extracorporeal glass transition start temperature + Extracorporeal glass transition end temperature) / 2.

[0078] (6) Maximum valley depth Sv Each parameter was measured and calculated in accordance with ISO 25178-2:2012 and 25178-3:2012. However, the measurements were performed using a scanning white light interference microscope "VS1540" (manufactured by Hitachi High-Tech Science Co., Ltd., measurement conditions and equipment configuration are described later). The captured image was interpolated (fully interpolated) using the included analysis software, and after surface correction using a quartic polynomial approximation, the image was processed with a median filter (3x3 pixels) and measured. The S-filter Nesting Index was set to 0.455. Measurements were performed on both sides of a 5cm x 5cm square piece of film. The intersection of the diagonals was designated as the first measurement point (starting point), and the second to fifth measurement points were determined at positions 1cm away from each of the four corners, for a total of five measurement positions. Measurements were taken at each measurement position, and the Sv of each measurement position was calculated according to the above procedure. The average value of each measurement position was adopted as the Sv of each surface of the film. <Measurement conditions and equipment configuration> Objective lens: 10x Telescope tube: 1x Zoom lens: 1x Wavelength filter: 530nm white Measurement mode: Wave Measurement software: VS-Measure 10.0.4.0 Analysis software: VS-Viewer 10.0.3.0 Measurement area: 561.1μm×561.5μm Pixel count: 1,024 x 1,024.

[0079] (7) Longitudinal thermal shrinkage rate after 30 minutes at 170°C A rectangular sample measuring 30 mm in length (measurement direction) and 10 mm in width was cut from the PAS film, with the longitudinal side as the longer side. A mark parallel to the width direction was made 5 mm inward from the center of each short side of the sample, and the length between the markings was defined as the trial length of 20 mm (L0). Next, the sample was placed between sheets of paper and heated in an oven maintained at 170°C for 30 minutes. After being removed and cooled to room temperature, the length between the two markings (L1) was measured, and the thermal shrinkage rate was calculated using the following formula. The same measurement was performed five times, and the arithmetic mean was taken as the thermal shrinkage rate in the longitudinal direction after 30 minutes at 170°C. Thermal shrinkage rate = {(L0-L1) / L0} × 100 (%).

[0080] (8) Evaluation of film dielectric breakdown voltage at 150°C The film was heated for 1 minute in an oven maintained at 150°C, and then measured in that atmosphere according to JIS C2330(2001)7.4.11.2 Method B (flat electrode method). The dielectric breakdown voltage test (measured above) was performed 30 times, and the obtained values ​​were divided by the film thickness (measured in (2) above) to obtain a total of 30 measured values ​​(calculated values). The 5 largest values ​​and the 5 smallest values ​​were excluded from the 20 values, and the average of the 10 smallest values ​​was calculated and taken as the film dielectric breakdown voltage at 150°C. The film dielectric breakdown voltage at 150°C was evaluated as follows from the obtained film dielectric breakdown voltage at 150°C. S: The film dielectric breakdown voltage at 150°C was 330V / μm or higher. A: The film dielectric breakdown voltage at 150°C was between 300V / μm and 330V / μm. B: The film dielectric breakdown voltage at 150°C was between 240V / μm and 300V / μm. C: The film dielectric breakdown voltage at 150℃ was between 210V / μm and 240V / μm. D: The film dielectric breakdown voltage at 150°C was less than 210V / μm, or the film shrinkage was so large that evaluation was not possible.

[0081] (8) Evaluation of film capacitor characteristics (reliability at 150°C) Film winding inner surface: 25 W·min / m 2 Corona discharge treatment was performed in air at the specified treatment intensity. Next, aluminum was deposited on the corona discharge treated surface using a deposition pattern with a film resistance of 10 Ω / sq and a margin portion perpendicular to the longitudinal direction, a so-called T-shaped margin (with a longitudinal pitch (period) of 17 mm and a fuse width of 0.5 mm due to masking oil) (a vacuum deposition machine manufactured by ULVAC, Inc. was used for deposition). Subsequently, the obtained deposition material was slit to obtain a deposition reel with a film width of 50 mm (end margin width of 2 mm). Next, film capacitor elements were wound using a component winding machine (KAW-4NHB) manufactured by Kaito Seisakusho Co., Ltd., subjected to metallizing treatment, and then heat-treated at 170°C for 5 hours under reduced pressure, to which lead wires were attached to finish the film capacitor elements. Ten of these film capacitor elements were subjected to a DC voltage of 150 V / μm at a high temperature of 150°C, and tanδ was measured every 100 hours. For each film capacitor element, the time at which its tanδ exceeded 200% of its initial value was identified, and the average value was used as the lifespan of the film capacitor element. It was evaluated according to the following criteria: A means usable, B means poor practical performance, and C means unusable. The shape of the film capacitor element was observed visually. The shape of a film capacitor element can deform due to dielectric breakdown of the film or thermal shrinkage. A: The lifespan was over 500 hours, and there was no deformation of the film capacitor element. B: Although the lifespan was over 500 hours, distortion was observed in the shape of the film capacitor element. C: The lifespan of the film capacitor element was less than 500 hours.

[0082] [Raw materials, film] <Coating liquid for forming resin layer A> Urethane acrylate 1: Product name "UV-3500BA", butyl acetate diluted urethane acrylate, manufactured by Mitsubishi Chemical Corporation. 2-Butanone: Manufactured by Fujifilm Wako Pure Chemical Corporation Omnirad 184: 1-Hydroxycyclohexyl phenyl ketone manufactured by IGM Resins B.V.

[0083] <PPS resin> (Reference Example 1-1) A 1-kiloliter SUS vessel equipped with a stirrer was charged with 1 kmol of 47 mass% aqueous sodium hydrosulfide solution, 1.02 kmol of 47 mass% aqueous sodium hydroxide solution, 1.65 kmol of N-methyl-2-pyrrolidone (NMP), 0.3 kmol of sodium acetate, and 100 kg of ion-exchanged water. The mixture was gradually heated to 235°C over about 180 minutes while stirring at 240 rpm and passing nitrogen at normal pressure, after distilling off 204 kg of water and 0.4 kg of NMP, the reaction vessel was cooled to 160°C. The amount of scattered hydrogen sulfide was 0.02 kmol. To the residual mixture were added 0.002 kmol of 1,2,4-trichlorobenzene, 1.05 kmol of p-dichlorobenzene (p-DCB), and 1.35 kmol of NMP. Subsequently, the reaction vessel was sealed under nitrogen gas. While stirring at 400 rpm, the temperature was raised from 160°C to 270°C over 140 minutes, the reaction was carried out at 270°C for 130 minutes, and then cooled from 270°C to 200°C over 100 minutes. Simultaneously with the start of cooling, 0.8 kmol of water was injected into the system over 10 minutes, and after reaching 200°C, the system was rapidly cooled to near room temperature using a blower. The content was taken out, 1 kiloliter of NMP was added, and the mixture was stirred at 85°C for 30 minutes, then the solvent and solid matter were filtered off through a sieve (80 mesh). To the obtained solid matter, 1 kiloliter of NMP was added, the mixture was stirred at 85°C for 30 minutes, and then filtered off. The operation of adding 1 kiloliter of warm water to the obtained solid matter, stirring at 70°C for 30 minutes, and filtering off was repeated 3 times. To the obtained solid matter, 1 kiloliter of warm 0.005 mass% aqueous calcium acetate solution was added, the mixture was stirred at 70°C for 30 minutes, and then filtered off. The operation of adding 1 kiloliter of warm water to the obtained solid matter, stirring at 70°C for 30 minutes, and filtering off was repeated 2 times. The solid matter thus obtained was dried under reduced pressure at 120°C for 5 hours, to obtain crosslinked PPS resin 1 having a melt flow rate (MFR) of 3 g / 10min, a dw / dlog(M) value of 0.6 at log(M)=5, and a glass transition temperature of 92°C.

[0084] (Reference Example 2-1) A 1-kiloliter SUS vessel equipped with a stirrer was charged with 1.01 kmol of 47 mass% sodium hydrosulfide aqueous solution, 1.04 kmol of 47 mass% sodium hydroxide aqueous solution, 1.6 kmol of N-methyl-2-pyrrolidone (NMP), 0.3 kmol of sodium acetate, and 100 kg of ion-exchanged water. While stirring at 240 rpm and introducing nitrogen at normal pressure, the mixture was gradually heated to 235°C over about 180 minutes. After distilling out 209 kg of water and 0.4 kmol of NMP, the reaction vessel was cooled to 160°C. The amount of scattered hydrogen sulfide was 0.02 kmol. To the residual mixture, 0.99 kmol of p-dichlorobenzene (p-DCB) and 2.40 kmol of NMP were added. Subsequently, the reaction vessel was sealed under nitrogen gas, the temperature was raised from 160°C to 230°C over 90 minutes while stirring at 400 rpm, and the reaction was carried out at 230°C for 280 minutes. Then, the temperature was raised from 220°C to 250°C over 60 minutes, 0.8 kmol of water was injected into the system over 10 minutes, and the reaction was continued for 320 minutes. Thereafter, the mixture was cooled from 255°C to 200°C over 100 minutes. After reaching 150°C, the mixture was quenched to near room temperature using a blower. The content was taken out, 1 kiloliter of NMP was added, and the mixture was stirred at 85°C for 30 minutes, then the solvent and the solid matter were separated by filtration through a sieve (80 mesh). To the obtained solid matter, 1 kiloliter of NMP was added, the mixture was stirred at 85°C for 30 minutes, and then filtered. The operation of adding 1 kiloliter of warm water to the obtained solid matter, stirring at 70°C for 30 minutes, and filtering was repeated 3 times. To the obtained solid matter, 4.5 kg of calcium acetate monohydrate and 1 kiloliter of warm water as an aqueous solution were added, the mixture was stirred at 70°C for 30 minutes, and then filtered. The operation of adding 1 kiloliter of warm water to the obtained solid matter, stirring at 70°C for 30 minutes, and filtering was repeated 2 times. The solid matter thus obtained was dried under reduced pressure at 120°C for 5 hours to obtain PPS Resin 2 having a dw / dlog(M) value of 0.8 at log(M)=5 and a glass transition temperature of 92°C.

[0085] <PPS pellets, masterbatch of PPS granules and particles> (Reference Example 1-2) PPS resin 1 was fed into a vented, co-rotating twin-screw compounding extruder heated to 320°C, melted and extruded to produce strands, cooled with water at 25°C, and immediately cut to produce PPS pellets 1.

[0086] (Reference example 2-2) PPS resin 2 was fed into a vented, co-rotating twin-screw compounding extruder heated to 320°C, melted and extruded to produce strands, cooled with water at 25°C, and immediately cut to produce PPS pellets 2.

[0087] (Reference Example 1-3) Preparation of Masterbatch (MB1) of PPS resin and thermoplastic resin A co-rotating, vented twin-screw kneading extruder equipped with one kneading paddle section was heated to 320°C. 85 parts by mass of PPS resin 1 obtained in Reference Example 1-2 and 15 parts by mass of polyethersulfone (PESU: Solvay Advanced Polymers Co., Ltd., "Belladel" (registered trademark) 3600, glass transition temperature 225°C) dried at 120°C for 3 hours under reduced pressure of 1 mmHg were supplied through the feed port. After melt-kneading at a screw rotation speed of 200 rpm, the mixture was extruded in strand form, cooled with water at 25°C, and immediately cut to produce a masterbatch (MB1) containing 10 parts by mass of PPSU.

[0088] (Reference Example 1-4) Preparation of PPS resin and particle masterbatch (MB2) A particle masterbatch (MB2) with a particle content of 10% by mass was prepared in the same manner as in Reference Example 1-3, except that a mixture of 90% by mass of PPS resin 1 and 10% by mass of calcium carbonate (average particle size 1.0 μm) as inert particles was melt-kneaded.

[0089] (Reference Example 2-3) Preparation of a masterbatch (MB3) of PPS resin and thermoplastic resin A co-rotating, vented twin-screw kneading extruder equipped with one kneading paddle section was heated to 320°C. 85 parts by mass of PPS resin 2 and 15 parts by mass of polyethersulfone (PESU: Solvay Advanced Polymers Co., Ltd., "Belladel" (registered trademark) 3600), dried at 120°C for 3 hours under reduced pressure of 1 mmHg, were supplied through the feed port. After melt-kneading at a screw rotation speed of 200 rpm, the mixture was extruded in strand form, cooled with water at 25°C, and immediately cut to produce a masterbatch (MB3) containing 10 parts by mass of PESU.

[0090] (Reference Example 2-4) Preparation of PPS resin and particle masterbatch (MB4) A particle masterbatch (MB4) with a particle content of 10% by mass was prepared in the same manner as in Reference Example 2-3, except that a mixture of 90% by mass of PPS resin 2 and 10% by mass of calcium carbonate (average particle size 1.0 μm) as inert particles was melt-kneaded.

[0091] (Reference Example 2-5) Preparation of PPS resin and particle masterbatch (MB5) A particle masterbatch (MB5) with a particle content of 10% by mass was prepared in the same manner as in Reference Example 2-4, except that a mixture of 90% by mass of PPS resin 2 and 10% by mass of silica (average particle size 0.4 μm, Si content 46%) as inert particles was melt-kneaded.

[0092] (Reference Example 3-1) Preparation of a masterbatch (MB6) of PPS resin and PESU 70 parts by mass of PPS resin 1, 30 parts by mass of polyethersulfone (PESU: Solvay Advanced Polymers Co., Ltd., "Belladel" (registered trademark) 3600, glass transition temperature 225°C) dried at 120°C for 3 hours under reduced pressure of 1 mmHg, and 2.4 parts by mass of γ-isocyanate-topropyltriethoxysilane (Shin-Etsu Chemical Co., Ltd., "KBE9007") were uniformly mixed under dry air. The mixture was then fed into a twin-screw compounding extruder with vents and three kneading paddle sections (manufactured by Japan Steel Works, screw diameter 30 mm, screw length / screw diameter = 45.5), melt-extruded at 330°C with a residence time of 90 seconds and a screw rotation speed of 300 rpm, extruded in strand form, cooled with water at 25°C, and immediately cut to produce a masterbatch (MB6).

[0093] (Example 1) As raw materials for resin layer B, 69 parts by mass of PPS pellets 2, 30 parts by mass of MB3, and 1 part by mass of MB4 were mixed, and the mixture was dried under reduced pressure at 180°C for 3 hours, and then fed to a single-screw extruder whose melting zone was heated to 325°C. Next, the molten polymer was passed through a fiber-sintered stainless steel metal filter (20 μm cut), melt-extruded from the die lip of a T-die set at a temperature of 320°C, and then closely adhered to a cast drum with a surface temperature of 25°C while applying an electrostatic charge for cooling and solidification, to obtain an unstretched film with a thickness of 50 μm. Next, using a longitudinal stretching machine composed of a plurality of heated roll groups, the obtained unstretched film was stretched at a stretching temperature of 105°C in the longitudinal direction of the film at a magnification of 3.5 times by utilizing the peripheral speed difference of the rolls. Then, using the peripheral speed difference of the rolls, a relaxation treatment was performed at 102°C so that the film shrank by 1.0% in the longitudinal direction. Thereafter, both widthwise end portions of the obtained uniaxially stretched film were held by a plurality of clips and guided to a tenter, and stretched at a stretching temperature of 102°C in the width direction at a magnification of 3.1 times. Subsequently, a heat treatment was performed at 280°C, followed by a 2% relaxation treatment, and after cooling to room temperature, the film edges were removed to obtain a film (resin layer B) with a thickness of 4.0 μm. Thereafter, the surface of resin layer B that had been in contact with the cast drum was subjected to corona treatment, and a coating liquid prepared by mixing urethane acrylate 1, 2-butanone, and α-hydroxyalkylphenone ("Omnirad" (registered trademark) 184) at a mass ratio of 100:900:0.3 was uniformly applied onto the treated surface using a bar coater so that the thickness after curing would be the thickness of resin layer A (200 nm) shown in Table 1, followed by drying in a drying oven at 90°C for 1 minute. Subsequently, the coated film was introduced into a UV irradiation apparatus, with an illuminance of 50 mW / cm 2 , and an irradiation dose of 0.1 J / cm 2 , and the coating film was cured under the condition of an oxygen concentration of 100 ppm to form resin layer A. Then, the laminate of resin layer A and resin layer B was wound up such that resin layer A became the inner winding surface, to obtain a PAS film. The evaluation results are shown in Table 1.

[0094] (Examples 2 to 8, Comparative Examples 1 to 5) Films for film capacitors were obtained in the same manner as in Example 1, except that the raw material formulations and film-forming conditions for resin layer A and resin layer B were as shown in Table 1. The evaluation results are shown in Table 1. In Comparative Examples 4 and 5, the coating solution was not applied, and resin layer A was not provided.

[0095] [Table 1] [Industrial applicability]

[0096] The polyarylene sulfide film of the present invention exhibits excellent dielectric strength in high-temperature environments. Therefore, by using it as a dielectric in film capacitors, the long-term stability of the film capacitors can be improved.

Claims

1. A polyarylene sulfide film in which, when the longitudinal Raman orientation parameter is Rd1 and the widthwise Raman orientation parameter is Rd2, (Rd1 + Rd2) / 2 is between 8.3 and 15.0, and the longitudinal thermal shrinkage rate after heating at 170°C for 30 minutes is between -5.0% and 5.0%.

2. A polyarylene sulfide film according to claim 1, comprising a resin with a glass transition temperature of 170°C or higher and 300°C or lower.

3. The polyarylene sulfide film according to claim 1 or 2, wherein the Sv of at least one surface is 0.00010 μm or more and 1.0 μm or less.

4. The polyarylene sulfide film according to claim 1 or 2, wherein, in the molecular weight distribution measured by GPC, the dw / dlogM value of the polyarylene sulfide component with logM=5 is 0.70 or more and 10 or less.

5. A polyarylene sulfide film according to claim 1 or 2, comprising a polyethersulfone.

6. The polyarylene sulfide film according to claim 1 or 2, wherein the silicon atom content is 0 ppm or more and 3500 ppm or less when the total mass of the film is 100% by mass.

7. The polyarylene sulfide film according to claim 1 or 2, wherein at least one of the outermost layers has a resin layer A in which polyarylene sulfide is not the main component.

8. The polyarylene sulfide film according to claim 7, wherein the resin layer A comprises at least one compound selected from the group consisting of urethane acrylate polymer, acrylate polymer, urethane methacrylate polymer, methacrylate polymer, aliphatic polyether, aliphatic polyester, aliphatic polyamide, polyurethane, and polyurea.

9. A metal laminate having a metal layer on at least one surface of the polyarylene sulfide film according to claim 1 or 2.

10. A film capacitor comprising the metal laminate described in claim 9.

11. A power control unit having the film capacitor described in claim 10.

12. An electric vehicle having the power control unit described in claim 11.

13. An electric aircraft having the power control unit described in claim 11.

Citation Information

Patent Citations

  • Transparent biaxially oriented polyyppphenylene sulfide film

    JP1979142275A

  • Poly-p-phenylene sulfide film

    JP1982187327A

  • capacitor

    JP1987158312A

  • Biaxially oriented film, metallized film and film capacitor

    JP2001261959A

  • Biaxially oriented polyarylene sulfide film, metallized film and capacitor

    JP2008280508A